"I Was Like Damaged, Used Goods": Thematic Analysis of Disclosures of Childhood Sexual Abuse to Romantic Partners. Issue 6 (17th August 2016) - MacIntosh, Heather; Fletcher, Kara; Collin-Vézina, Delphine
ABSTRACT: A thematic analysis of the reported experiences of childhood sexual abuse (CSA) survivors in disclosing their CSA history to romantic partners was completed with the goal of learning about the experience of their disclosure and to consider role partners may play in the disclosure experiences of CSA survivors. Transcripts of 19 survivors were analyzed using a standard thematic analysis methodology. Two global themes emerged, reasons for disclosing and impact of response, and these were highly interrelated by shame. A preliminary theory of disclosing to romantic partners was posited.